Adventure tourism management - Buckley, Ralf (Amsterdam : Elsevier Science, 2010)
The academic study of the Adventure Tourism is rapidly increasing in popularity, with research beginning to focus on it heavily. This book offers a comprehensive look at this multi-million dollar industry sector from a variety of perspectives relevant to the teaching of tourism.
1. Introduction -- 2. Trends and Patterns -- 3. Economics Product Patterns -- 4. Geography -- 5. Products and Prices -- 6. Marketing -- 7. Guiding -- 8. Communications -- 9. Experience and Motivations Subsectors -- 10. Subsectors -- 11. Wildlife -- 12. Marine -- 13. Helitourism -- 14. Boardsports Key Issues -- 15. Amenity Migration -- 16. Environmental Management -- 17. Risk Management -- 18. Climate Change -- 19. Conclusions.
Includes bibliographical references and index.
Keywords: ADVENTURE TRAVEL